Pertanggung Jawaban Hukum Produsen Terhadap Hilangnya Keanekaragaman Hayati Mikroba Tanah Akibat Penggunaan Pestisida - Dwi Nila Seni Wati; Emy Rosnawati (Journal Customary Law, 2025)
The massive use of pesticides in modern agriculture not only increases productivity but also has a negative impact on the environment, particularly the loss of soil microbial biodiversity. Soil microbes play an important role in maintaining soil fertility and ecosystem balance. This study aims to analyze the responsibility of pesticide manufacturers for the loss of soil microbial biodiversity due to pesticide use. The method used is normative juridical with a statute approach. Primary legal materials include Law No. 32 of 2009 concerning environmental protection and management. Secondary legal materials include books, journals, and scientific articles relevant to this study. The results show that the protection of soil microbes has not been explicitly regulated, although pesticide producers can be held accountable through administrative, civil, and criminal mechanisms, including the principle of strict liability.